Antonymy In Space And Other Strictly Ordered Domains - Jessica Rett (Baltic International Yearbook of Cognition, Logic and Communication, 2015)
Natural language references different types of entities. Some of these entities (e.g. degrees, locations, times) are strictly ordered with respect to one another; others (e.g. individuals, possible worlds) are not. The empirical goal of this paper is to show that some linguistically encoded relations across these domains (e.g. under, slower than) display a polar asymmetry, while others do not. The theoretical goal of this paper is to argue that this asymmetry – and its restriction to only certain relations – is due to intrinsic properties of strictly ordered domains, coupled with a bias in how language users perceive these domains.
Keywords: natural language; antonymy; strictly ordered domains; formal semantics; distinct domains; distinct entities